Ethics out of economics - Broome, John (Cambridge University Press, 2013)
Many economic problems are also ethical problems: should we value equality? How much should we care about preserving the environment? How should medical resources be divided between saving life and enhancing life? It also turns out that many of the formal techniques of economics can do important work in ethical theory. In particular, utility theory can help analyse the structure of good. Ethics out of Economics examines some of the theoretical and practical issues that lie between economics and ethics, and especially aims to show how utility theory can contribute to ethics.